Billionaires in world politics: donors, governors, authorities. Issue 2 (4th May 2022) - Dingwerth, Klaus; Eckl, Julian
ABSTRACT: Hägel's book is timely. As economic inequality has been on the rise, the increasing number of billionaires and their political activities have come under public scrutiny. The book contributes to such scrutiny and allows to ask questions about responsibility, accountability, and legitimacy. It also adds to scholarship on individuals in world politics. Our comment provides a critical discussion of two specific aspects of Hägel's analysis. First, we clarify that most of the book focuses on billionaires as transnational actors while few billionaires seem to exert influence on broader structures or processes of global governance. This clarification helps to understand the character of billionaires' activities in world politics. Second, we reverse the perspective from which Hägel looks at billionaires. We point out that, while Hägel tends to look over the shoulders of the billionaires and mainly observes how they exercise influence in world politics, we argue that the other actors matter, too. More specifically, we maintain that billionaires' roles in global governance are shaped through their specific recognition by international society (state actors) and/or by world society (non-state actors). This change in perspective sheds additional light on the conditions that affect the role(s) billionaires can play in world politics.